Konstruktives Auflösen. Über ein radikales Museumskonzept für das Dollfuß-Geburtshaus und sein jähes Ende - Remigio Gazzari; Christian Rabl; Johanna Zechner (Österreichische Zeitschrift für Geschichtswissenschaften)
New focal point of OeZG: examining recent developments and debates in Austria’s museum and exhibition landscape. In their essay, Remigio Gazzari, Christian Rabl, and Johanna Zechner explore the planned but ultimately unrealized redesign of the birthplace of Austrofascist chancellor Engelbert Dollfuß in Texingtal, Lower Austria. They offer direct insights into the political controversies surrounding the former museum and its abrupt closure.